The Association of Stress with the Occurrence of Recurrent Aphthous Stomatitis (RAS) Amid the COVID-19 Pandemic in Students of Senior High School - Medawati, Ana; Andriani, Ika; Driana Rahmawati, Atiek; Femilian, Afryla; Nur Arifta, Arum; Adi Saputra, Septian (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
The most prevalent oral mucosal lesion is Recurrent Aphthous Stomatitis (RAS). SAR can occur due to local trauma, stress, drug use, hormonal changes, nutritional deficiencies, immunological factors, smoking, hereditary and genetic factors, microbial factors, food hypersensitivity, hematinic deficiencies, and human immunodeficiency (HIV) infection. RAS is a prevalent condition that is defined by the presence of round ulcers that appear as recurrent lesions, numerous, small, round, have a yellowish base, and are surrounded by an erythematous halo and can occur in young and adult ages. Specifically, the pandemic caused by COVID-19 has affected people's lives around the world, including senior high school students. The incidence of RAS in adolescents is categorized as high; according to the findings of RISKESDAS, the percentage is 8.7%. Stress is a contributing component to the development of RAS. The objective of this investigation was to ascertain the correlation between stress and the prevalence of RAS during the COVID19 pandemic. This investigation employed a cross-sectional design and was observational analytic. A total of 104 research subjects were included in the study, which was conducted on students at SMA Negeri 6 in Yogyakarta. The results revealed 59 respondents with normal stress levels, of which 57 respondents (54.8%) were positive for RAS. The Spearman Rank correlation statistical test was employed to analyze the data, resulting in a significant value of p = 0.019 or <0.05, which denotes a correlation stress and the occurrence of RAS during the COVID-19 pandemic in students at SMA 6 Yogyakarta, serving as the conclusion